Association between Parental Treatment and Aggressive Behaviors among Adolescent Students - Mohammed, Qahtan Qasim (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study aims at assessing the parental treatment and aggressive behaviors among adolescents and to find out the association between parental treatment and aggressive behavior. Methodology: A descriptive correlational design that is initiated for the period of January 1st to July 5th, 2021; The sample of the study includes 220 from the intermediate school male students in schools in the Karkh and Rusafa in Baghdad have ranged in age from (13-15) years, the researcher used the convenient sampling method (non-probability sample) in which the students were selected purposively. Parental Treatment Scale and Aggressive Behavior Scale were used for achieving the goals of current study. The data have been collected through the utilization of the self-administrative report as a mean of data collection. Statistical analyses were conducted by using statistical package for social science (IBM SPSS Statistics) version 26.0. Results: The study found that the majority of the students’ parents have moderate (good) awareness regarding parenting treatment to deal with their sons (80%). The students are showing moderate level of aggressive behavior towards others, self and properties (56.4%, 47.3%, and 50.9%). There is high significant association between parental treatments and aggressive behavior towards others and self at p-value= 0.001, 0.005 respectively Recommendations: The study recommends that administration of educational institutions should have the role in focusing on school counsellor as well as educate the parents how to deal with their children. Keywords: Parental treatment, Aggressive behavior, Adolescents